2020
DOI: 10.3390/met10030407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Laser-Arc Hybrid Welding for AA6082-T6 Aluminum Alloy with Two Different Arc Modes

Abstract: The effects of arc modes on laser-arc hybrid welding for AA6082-T6 aluminum alloy were comparatively studied. Two arc modes were employed: pulsed metal inert gas arc and cold metal transfer arc. The results indicated that joints without porosity, undercutting, or other defects were obtained with both laser-pulsed metal inert gas hybrid welding (LPMHW) and laser-cold metal transfer hybrid welding (LCHW). Spatter was reduced, and even disappeared, during the LCHW process. The sizes of equiaxed dendrites and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The highest tensile strength of the joint was approximately 54%, corresponding to the strength of the base metal. Han et al [ 53 ] comparatively studied a 6 mm 6082-T6 aluminum alloy butt joint welded by laser-cold metal transfer hybrid welding and laser-pulsed metal inert gas hybrid welding, and the results showed that the softening degree and range of HAZ with laser-cold metal transfer hybrid welding were smaller than those achieved with laser-pulsed metal inert gas hybrid welding. In addition, the joint efficiency of laser-cold metal transfer hybrid welding could reach 84.7%, which was higher than that of the laser-pulsed metal inert gas hybrid welding, which was 82.4%.…”
Section: Low-heat-input Weldingmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest tensile strength of the joint was approximately 54%, corresponding to the strength of the base metal. Han et al [ 53 ] comparatively studied a 6 mm 6082-T6 aluminum alloy butt joint welded by laser-cold metal transfer hybrid welding and laser-pulsed metal inert gas hybrid welding, and the results showed that the softening degree and range of HAZ with laser-cold metal transfer hybrid welding were smaller than those achieved with laser-pulsed metal inert gas hybrid welding. In addition, the joint efficiency of laser-cold metal transfer hybrid welding could reach 84.7%, which was higher than that of the laser-pulsed metal inert gas hybrid welding, which was 82.4%.…”
Section: Low-heat-input Weldingmentioning
confidence: 99%
“…Low-heat-input welding: such as laser beam welding (LBW), friction stir welding (FSW), and cold metal transfer (CMT) welding. To improve the mechanical properties of age-hardening aluminum alloy joints welded by the low heat input technique, researchers have focused on how to eliminate welding defects [ 41 , 42 , 43 , 44 ], optimize welding parameters [ 45 , 46 , 47 ] and innovate the technique [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zhang et al [35] also indicated that the spatter during the laser-arc hybrid welding process was significantly less than that during the pure arc welding process. Han et al [36] analyzed the spatter in a laser-pulsed MIG hybrid welding and laser-CMT hybrid welding process, finding less or no spattering during laser-CMT hybrid welding.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their advantages (significant penetration depth, higher welding rates, and reduced filler metal consumption), hybrid laser technologies are investigated by numerous research centres around the world. Researchers use HLAW to join various structural materials including steel [ 12 , 13 ], titanium alloys [ 14 , 15 ], aluminium alloys [ 16 , 17 ], or dissimilar materials [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%